2021
DOI: 10.21608/ajas.2021.79364.1028
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Reference and Actual Evapotranspiration and Yield of Maize Under Different Irrigation Levels With Filter Mud Cake Applications

Abstract: Two experiments were conducted at Water Studies and Research Complex (WSRC), Station, National Water Research Center, Toshka -Abu Simbel, during two growing seasons of 2018 and 2019 to compare available reference evapotranspiration (ET • ) equations (Hargreaves-Samani (HS), Makkink (MK), Priestley-Taylor (PT) and Turc (TC)) to the FAO-56 method to determine suitable alternatives for use in Toshka region, and to evaluation effects of drought stress and filter mud cake on physiological traits of two maize hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Maximum ear area was observed for Xinyu 65 on sowing date E, followed by sowing date E for Huamei No. 1 in 2021, while lowest ear area was observed on sowing date A for KWS3376 corn; these results are close to those obtained by [37,38]. In 2022, the maximum ear area was seen for KWS9384 on sowing date C, while the minimum ear area was observed on sowing dates A and B for Xinyu 65.…”
Section: Discussionsupporting
confidence: 78%
“…Maximum ear area was observed for Xinyu 65 on sowing date E, followed by sowing date E for Huamei No. 1 in 2021, while lowest ear area was observed on sowing date A for KWS3376 corn; these results are close to those obtained by [37,38]. In 2022, the maximum ear area was seen for KWS9384 on sowing date C, while the minimum ear area was observed on sowing dates A and B for Xinyu 65.…”
Section: Discussionsupporting
confidence: 78%
“…Gonzalez et al [42], in their chemical analysis of this residue, found a pH(CaCl 2 ) of 8.2 and a total organic matter content of 29.6%. Additionally, filter cake decreases soil density and increases porosity, improving aeration and water retention capacity [48,49]. Along with these benefits, there are also gains in environmental and agricultural aspects [40,50].…”
Section: Results Of the Application Of Filter Cake To The Soil And In...mentioning
confidence: 99%
“…It is a major annual cereal crop in Egypt and other Mediterranean countries, which has the third largest crop after wheat and rice with a total area under cultivation reaching about 900,000 hectares in 2019/2020, producing about 7.2 million metric tons (El-Dissoky et al 2017;Wally and Mariano 2019). Moreover, according to Abaza et al (2021) and Abaza (2022), the average daily evaporation when corn planting in February in the study area of the experiment ranges between 10.45 and 0.89 mm per day, and the crop lasts for an average growth period, reaching 93 days, with a total gross water requirement up to 10,890 m −3 ha −1 .…”
Section: Introductionmentioning
confidence: 99%